Interconnected network protection systems - the basis for the reliable and safe operation of distribution grids with a high penetration of renewable energies and electric vehicles - Lorenz, Matthias; Pletzer, Tobias Markus; Schuhmacher, Malte; Sowa, Torsten; Dahms, Michael; Stock, Simon; Babazadeh, Davood; Becker, Christian; Jäger, Johann; Lorz, Tobias; Dahlmanns, Markus; Fink, Ina Berenice; et al. (IET Conference Proceedings, 2022)
Power grids are increasingly faced with the introduction of decentralized, highly volatile power supplies from renewable energies and high loads occurring from e-mobility. However, today's static grid protection cannot manage all upcoming conditions while providing a high level of dependability and security. It forms a bottleneck of a future decarbonizing grid development. In our research project, we develop and verify an adaptive grid protection algorithm. It calculates situation dependent protection parameters for the event of power flow shifts and topology changes caused by volatile power supplies due to the increase of renewable generation and the rapid expansion of e-mobility. As a result the distribution grid can be operated with the optimally adapted protection parameters and functions for changing operating states. To safely adjust the values on protection hardware in the field, i.e., safe from hardware failures and cyberattacks, we research resilient and secure communication concepts for the adaptive and interconnected grid protection system. Finally, we validate our concept and system by demonstrations in the laboratory and field tests.
CRIS-Team Scopus Importer:2024-12-16